Bio-inspired Panel Design for Thermal Management. (2015) - Portilla-Aguilar, J.M.; Sánchez-Hernández, L.M.; Mayorga, M; Romero-Salazar, L.; Arteaga-Arcos, J.C.
Abstract: Based in the fact that one of the most imperative action lines regarding the sustainability of manufactured products and services is the management of the total energy consumption, we design a thermal management device inspired in the polar bear's hair that consist of hollow cylinders, such that exposed to direct solar radiation shows a good performance as a thermal insulator. We conducted experimental measurements of temperature in a closed system exposed to direct solar radiation and observed that the temperature in the bio-inspired panel was at least 20% lower than the one registered in the surroundings. By means of numerical simulations we additionally show how the panel could be useful to improve the heat exchange exploiting the convection phenomena when varying the geometry of the proposal.